A bone repair 3D printing material, a bone repair scaffold and a preparation method thereof
Patent Information
- Application Number
- CN202610573598.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-28
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-04-28
AI Technical Summary
传统丝素蛋白水凝胶生物相容性优异,但存在湿态力学强度低、表面疏水、生物活性不足等缺陷
1、本发明在甲基丙烯酰化丝素蛋白的前体溶液中,创新性地引入了小分子L-亮氨酸,并结合光固化3D打印与乙醇后处理工艺。从分子机理上分析,一方面,乙醇诱导了丝素蛋白大分子由无规卷曲向稳定的β-折叠构象转变;另一方面,L-亮氨酸通过极其丰富的非共价相互作用与甲基丙烯酰化丝素蛋白交联骨架发生物理锚合,有效增强了高分子网络链段间的分子级约束力,限制了受力状态下的网络形变,这种基于化学与物理双重强化的协同机制,在不牺牲支架高孔隙率和连通微孔结构的前提下,将水凝胶支架的宏观压缩模量从约0.2MPa显著跃升至约0.85MPa,由此,本发明支架既能为骨修复早期提供坚实的生物力学支撑,又能防止因受力塌陷导致的孔道闭塞。
Smart Images

Figure CN122124323B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomedical materials technology, specifically to a bone repair 3D printing material, a bone repair scaffold, and a method for preparing the same. Background Technology
[0002] Bone defect repair and reconstruction is a major challenge in orthopedic and maxillofacial surgery. Autologous bone grafts have limited sources and pose risks of donor site complications; allogeneic and xenogeneic bone grafts carry risks of immune rejection and pathogen transmission. Traditional silk fibroin hydrogels have excellent biocompatibility, but suffer from drawbacks such as low wet mechanical strength, hydrophobic surface, and insufficient bioactivity.
[0003] Existing bone repair materials mostly rely on loading exogenous growth factors such as BMP-2 and VEGF to induce osteogenic or angiogenesis. However, the preparation and purification of these protein molecules are complex and costly, and they have short half-lives and poor stability in vivo. They often require supraphysiological doses to be effective. High-dose local or long-term application also faces safety risks such as ectopic osteogenic formation, severe inflammatory reactions, and even potential carcinogenic risks, making it difficult to meet the needs of safe and efficient clinical application.
[0004] Meanwhile, traditional stents have low molding precision and uncontrollable pore structure. Large-volume defects are prone to central necrosis due to insufficient vascularization, resulting in a low repair success rate.
[0005] Therefore, there is an urgent clinical need for a new type of bone repair material that can both simulate the natural bone microenvironment and possess appropriate mechanical strength, and achieve efficient osteogenic and vascularized synergistic regeneration without relying on expensive and high-risk exogenous growth factors. Summary of the Invention
[0006] In view of the common defects of existing bone repair scaffolds, especially traditional hydrogel scaffolds and allogeneic and autologous bone graft materials in terms of shape adaptability, mechanical properties, interfacial hydrophilicity, safety and ability to promote bone-vascular coupling, this invention provides a bone repair 3D printing material, a bone repair scaffold and its preparation method.
[0007] To achieve the above objectives, the present invention provides the following technical solution: A bone repair 3D printing material, comprising photocurable modified silk fibroin and bioactive small molecules, wherein the photocurable modified silk fibroin is methacrylamide silk fibroin; wherein the bioactive small molecules are branched-chain amino acids, and the bioactive small molecules are uniformly dispersed in the precursor solution of the photocurable modified silk fibroin by physical blending, and anchored to the gel network by non-covalent interactions after photocrosslinking; The nominal loading concentration of the bioactive small molecule in the precursor solution ranges from 100 ng / mL to 700 ng / mL; The branched amino acid is selected from L-leucine.
[0008] Preferably or optionally, the nominal loading concentration is 300 ng / mL.
[0009] Preferably or optionally, the photocured modified silk fibroin is acrylated silk fibroin or thiol-olefin modified silk fibroin.
[0010] On the other hand, the present invention also provides a bone repair scaffold, which is obtained by photopolymerization 3D printing using the above-mentioned bone repair 3D printing material. The scaffold has a porous structure designed and constructed by computer-aided design, with a macroscopic pore size of 500-1000μm and a porosity of 40%-60%.
[0011] Thirdly, the present invention also provides a method for preparing a bone repair scaffold, comprising the following steps: Step 1: Dissolve the photoinitiator and bioactive small molecules in a buffer solution, add the photocurable modified silk fibroin powder, mix and dissolve under light-protected conditions to obtain a homogeneous and clear composite precursor solution; Step 2: Load the composite precursor solution into the material tank of the photopolymer 3D printer. Based on digital light processing technology, solidify layer by layer under preset light intensity and exposure time to form a wet hydrogel scaffold with preset macroscopic channels. Step 3: Immerse the wet hydrogel scaffold in an alcohol solution to induce a conformational change in silk fibroin and sterilize it. Then rinse and replace it with buffer solution to obtain the bone repair scaffold.
[0012] Preferably or optionally, in step one, the mass-volume concentration of the photocurable modified silk fibroin in the precursor solution is 15%-25%.
[0013] Preferably or optionally, in step two, the preset light intensity is 5-10 mW / cm², and the single-layer exposure time is 5-20 s.
[0014] Preferably or optionally, in step three, the alcohol solution concentration used for the alcohol treatment is 50%-100%, and the treatment time is 10-60 minutes.
[0015] Preferably or optionally, in step two, the photopolymerization 3D printer is a DLP printer, an SLA printer, or an LCD printer.
[0016] And the application of the aforementioned bone repair 3D printing materials in the preparation of bone tissue engineering scaffolds, drug sustained-release carriers, or cartilage repair materials.
[0017] The beneficial effects of this invention are: 1. This invention innovatively introduces the small molecule L-leucine into the precursor solution of methacrylamide silk fibroin, and combines it with photopolymerization 3D printing and ethanol post-processing. From a molecular mechanism perspective, on the one hand, ethanol induces the transformation of the silk fibroin macromolecule from random coil to a stable β-sheet conformation; on the other hand, L-leucine physically anchors with the methacrylamide silk fibroin cross-linked backbone through extremely rich non-covalent interactions, effectively enhancing the molecular-level constraint force between polymer network segments and limiting network deformation under stress. This synergistic mechanism based on dual chemical and physical reinforcement significantly increases the macroscopic compressive modulus of the hydrogel scaffold from approximately 0.2 MPa to approximately 0.85 MPa without sacrificing the scaffold's high porosity and interconnected microporous structure. Therefore, the scaffold of this invention can provide robust biomechanical support for early bone repair and prevent pore closure caused by stress collapse.
[0018] 2. This invention abandons the growth factor strategy and selects essential branched-chain amino acids as the core active components, which are loaded into the hydrogel network through homogeneous physical blending. Because small-molecule amino acids possess extremely high thermodynamic and photochemical stability, they do not undergo structural degradation or biological inactivation during photo-initiated crosslinking, thus ensuring the robustness of the preparation process.
[0019] 3. The invention reshapes the free energy distribution and hydration dynamics of the scaffold surface at the molecular level through the physical embedding of L-leucine. Rheological and physicochemical characterization confirms that the introduction of the polar group of L-leucine significantly enhances the ability of the cross-linked network to capture and retain water molecules. After the scaffold is implanted in the body, it can rapidly absorb the surrounding body fluid, providing a highly biomimetic water-containing microenvironment for the target cells, thereby significantly accelerating the directed chemotaxis, rapid adhesion and three-dimensional infiltration of cells into the deep network of the scaffold.
[0020] 4. L-Leucine was applied to 3D-printed scaffolds, and the optimal nonlinear parameter range for its biological efficacy was defined through rigorous in vitro and in vivo experiments. It not only significantly enhanced the transmembrane migration ability of bone marrow mesenchymal stem cells, early osteogenic differentiation activity, and osteogenic gene expression such as bone matrix proteins in the early stages, promoting the deposition of dense calcium nodules; simultaneously, its paracrine or direct transduction signals also activated the expression of traditional exogenous growth factors in human umbilical vein endothelial cells, inducing the formation of highly interconnected capillary-like networks. This invention successfully achieved synergistic coupling of osteogenic and angiogenic processes in both spatial and temporal dimensions using a single small molecule, effectively avoiding graft center necrosis and significantly improving the repair quality and vascular network density of large-segment critical bone defects. Attached Figure Description
[0021] Figure 1This invention provides a step-by-step diagram of the preparation of a porous composite 3D hydrogel scaffold by combining methacrylamide silk fibroin with L-leucine and combining it with photopolymerization 3D printing process. Figure 2 These are the structural images of the control group and three concentrations of L-leucine hydrogels under SEM scanning. Figure 3 Physicochemical properties characterization of the methacrylamide silk fibroin hydrogel scaffolds loaded with different concentrations of L-leucine in this invention: AB. Porosity measurement results; C. Uniaxial compression test curve; D. Swelling kinetics curve; EF. Water contact angle test image; G. In vitro degradation curve; H. Fourier transform infrared spectrum; IJ. Rheological test curve; Figure 4 Characterization of the hydrogel scaffold effect of the present invention: proliferation of bone marrow mesenchymal stem cells and vascular endothelial cells co-cultured with methacrylamide-loaded L-leucine hydrogel scaffolds of different concentrations (AB); CF live and dead cell fluorescence staining to show the survival status and differentiation of cells on each scaffold group. Figure 5 To evaluate the ability of the scaffolds of the present invention to promote osteogenic differentiation and mineralization in vitro: alkaline phosphatase staining and alizarin red staining of bone marrow mesenchymal stem cells cultured on L-leucine-loaded methacrylamide silk fibroin hydrogel scaffolds of different concentrations (A, B, E, F); immunofluorescence staining of C, D, GN showed the effect of each scaffold group on the expression of key osteogenic proteins (Runx2, COL-1, OCN) in bone marrow mesenchymal stem cells.
[0022] Figure 6 For the evaluation of the expression of key pro-angiogenic molecules in this invention: A, B, D, and GK immunofluorescence staining showed the effect of different concentrations of L-leucine-loaded methacrylamide silk fibroin hydrogel scaffolds on the expression of exogenous growth factors in vascular endothelial cells and the quantitative analysis of the expression of corresponding molecules; CF tube formation experiment showed the effect of each group of scaffolds on the ability of vascular endothelial cells to construct three-dimensional capillary networks.
[0023] Figure 7 For the evaluation of bone marrow mesenchymal stem cell migration in this invention: A, C, E, and G Transwell migration experiments showed the effects of different concentrations of L-leucine-loaded methacrylamide silk fibroin hydrogel scaffolds on the chemotactic migration of bone marrow mesenchymal stem cells and human umbilical vein endothelial cells; B, D, F, and H scratch experiments showed the effects of each group of scaffolds on the planar migration ability of the two cell types. Detailed Implementation
[0024] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] In the description of this invention, it should be understood that the terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," and "counterclockwise," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this invention.
[0026] Addressing the significant clinical challenges of graft core necrosis caused by delayed vascularization in the repair of large bone defects, simple biomaterials struggle to simultaneously meet the dual requirements of osteogenic and angiogenic processes. Traditional exogenous growth factors (such as BMP-2 and VEGF) also face translational bottlenecks due to high cost, easy inactivation, and potential immune risks. Therefore, this invention utilizes natural polymer materials, high-precision photopolymerization 3D printing technology, and a small molecule activity induction strategy to construct a biomimetic composite hydrogel scaffold based on synergistic osteogenic and angiogenic processes: L-leucine / methacrylamide silk fibroin (SilMA / L-Leu).
[0027] The matrix of this biomimetic scaffold is a SilMA hydrogel framework with a high-fidelity porous structure. In a specific implementation, a 20% (w / v) solution of methacrylamide silk fibroin (SilMA) precursor, supplemented with 0.25% (w / v) of a photoinitiator (such as LAP), is used to fabricate a scaffold with a fully connected network structure via photopolymerization 3D printing technology. This matrix not only retains the excellent biocompatibility and tunable degradation of natural silk fibroin, but also, through precise control using computer-aided design (CAD) programs, endows the scaffold with highly uniform macroscopic channels and microscopic pores. This multi-level porous structure effectively simulates the three-dimensional water-containing environment of the extracellular matrix (ECM) of natural bone tissue, greatly promoting nutrient transport, early angiogenesis, and deep cell infiltration. Example
[0028] like Figure 1 As shown, this embodiment provides a bone repair 3D printing material.
[0029] This bone repair 3D printing material was prepared using the following method: Step 1: Under light-protected conditions, LAP was dissolved in PBS at a concentration of 0.25% (w / v), and the specified amount of L-Leu solid was added and completely dissolved to prepare a working solution of LAP / PBS containing 100 ng / mL L-Leu. Subsequently, SilMA powder was added to a final concentration of 20% (w / v), and the solution was dissolved by shaking at 37°C in the dark for at least 3 hours to obtain a homogeneous, clear, and bubble-free SilMA@L-Leu (100 ng / mL) composite precursor solution.
[0030] Step 2: Construct a cylindrical 3D model with a diameter of 5mm and a height of 3mm using computer-aided design software. Design regularly arranged mesh channels inside the model, setting the macroscopic aperture to 800μm. After slicing the model, import it into a digital light processing photopolymerization 3D printer.
[0031] Transfer the precursor solution prepared in step two to the printer's feed tank, set the core printing parameters as follows: light source intensity 8mW / cm², single-layer exposure time 10 seconds, bottom layer exposure number 2 layers, start the equipment, and program-controlled ultraviolet light to expose layer by layer according to the slice pattern, so that the precursor solution photopolymerizes and solidifies, forming a wet hydrogel scaffold with a preset porous structure.
[0032] Step 3: After the printing process is complete, gently remove the formed wet scaffold from the construction platform and immerse it completely in 75% (v / v) ethanol solution for 30 minutes at room temperature. This process can induce a physical conformational change (β-sheet crystallization) of silk fibroin and has a sterilization effect. After soaking, transfer the scaffold to sterile PBS and rinse it thoroughly 3 times to completely replace the residual ethanol in the channels. Finally, seal the scaffold and store it in sterile PBS at 4°C for later use. Example
[0033] This embodiment provides a bone repair 3D printing material.
[0034] This bone repair 3D printing material was prepared using the following method: Step 1: Under light-protected conditions, LAP was dissolved in PBS at a concentration of 0.25% (w / v), and the specified amount of L-Leu solid was added and completely dissolved to prepare a working solution containing 300 ng / mL L-Leu. Subsequently, SilMA powder was added to a final concentration of 20% (w / v), and the solution was dissolved by shaking at 37°C in the dark for at least 3 hours to obtain a homogeneous, clear, and bubble-free SilMA@L-Leu (300 ng / mL) composite precursor solution.
[0035] Step 2: Construct a cylindrical 3D model with a diameter of 5mm and a height of 3mm using computer-aided design software. Design regularly arranged mesh channels inside the model, setting the macroscopic aperture to 800μm. After slicing the model, import it into a digital light processing photopolymerization 3D printer.
[0036] Transfer the precursor solution prepared in step two to the printer's feed tank, set the core printing parameters as follows: light source intensity 8mW / cm², single-layer exposure time 10 seconds, bottom layer exposure number 2 layers, start the equipment, and program-controlled ultraviolet light to expose layer by layer according to the slice pattern, so that the precursor solution photopolymerizes and solidifies, forming a wet hydrogel scaffold with a preset porous structure.
[0037] Step 3: After the printing process is complete, gently remove the formed wet scaffold from the construction platform and immerse it completely in 75% (v / v) ethanol solution for 30 minutes at room temperature. This process can induce a physical conformational change (β-sheet crystallization) of silk fibroin and has a sterilization effect. After soaking, transfer the scaffold to sterile PBS and rinse it thoroughly 3 times to completely replace the residual ethanol in the channels. Finally, seal the scaffold and store it in sterile PBS at 4°C for later use. Example
[0038] This embodiment provides a bone repair 3D printing material.
[0039] This bone repair 3D printing material was prepared using the following method: Step 1: Under light-protected conditions, LAP was dissolved in PBS at a concentration of 0.25% (w / v), and the specified amount of L-Leu solid was added and completely dissolved to prepare a working solution containing 700 ng / mL L-Leu. Subsequently, SilMA powder was added to a final concentration of 20% (w / v), and the solution was dissolved by shaking at 37°C in the dark for at least 3 hours to obtain a homogeneous, clear, and bubble-free SilMA@L-Leu (700 ng / mL) composite precursor solution.
[0040] Step 2: Construct a cylindrical 3D model with a diameter of 5mm and a height of 3mm using computer-aided design software. Design regularly arranged mesh channels inside the model, setting the macroscopic aperture to 800μm. After slicing the model, import it into a digital light processing photopolymerization 3D printer.
[0041] Transfer the precursor solution prepared in step two to the printer's feed tank, set the core printing parameters as follows: light source intensity 8mW / cm², single-layer exposure time 10 seconds, bottom layer exposure number 2 layers, start the equipment, and program-controlled ultraviolet light to expose layer by layer according to the slice pattern, so that the precursor solution photopolymerizes and solidifies, forming a wet hydrogel scaffold with a preset porous structure.
[0042] Step 3: After the printing process is complete, gently remove the formed wet scaffold from the construction platform and immerse it completely in 75% (v / v) ethanol solution for 30 minutes at room temperature. This process can induce a physical conformational change (β-sheet crystallization) of silk fibroin and has a sterilization effect. After soaking, transfer the scaffold to sterile PBS and rinse it thoroughly 3 times to completely replace the residual ethanol in the channels. Finally, seal the scaffold and store it in sterile PBS at 4°C for later use.
[0043] Comparative Example: This embodiment provides a bone repair 3D printing material.
[0044] This bone repair 3D printing material was prepared using the following method: Step 1: Under light-protected conditions, LAP was dissolved in PBS at a concentration of 0.25% (w / v), and then SilMA powder was added at a final concentration of 20% (w / v). The solution was then dissolved by shaking at 37°C in the dark for more than 3 hours to obtain a homogeneous, clear, bubble-free composite precursor solution.
[0045] Step 2: Construct a cylindrical 3D model with a diameter of 5mm and a height of 3mm using computer-aided design software. Design regularly arranged mesh channels inside the model, setting the macroscopic aperture to 800μm. After slicing the model, import it into a digital light processing photopolymerization 3D printer.
[0046] Transfer the precursor solution prepared in step two to the printer's feed tank, set the core printing parameters as follows: light source intensity 8mW / cm², single-layer exposure time 10 seconds, bottom layer exposure number 2 layers, start the equipment, and program-controlled ultraviolet light to expose layer by layer according to the slice pattern, so that the precursor solution photopolymerizes and solidifies, forming a wet hydrogel scaffold with a preset porous structure.
[0047] Step 3: After the printing process is complete, gently remove the formed wet scaffold from the construction platform and immerse it completely in 75% (v / v) ethanol solution for 30 minutes at room temperature. This process can induce a physical conformational change (β-sheet crystallization) of silk fibroin and has a sterilization effect. After soaking, transfer the scaffold to sterile PBS and rinse it thoroughly 3 times to completely replace the residual ethanol in the channels. Finally, seal the scaffold and store it in sterile PBS at 4°C for later use.
[0048] To evaluate the three-dimensional microstructure and pore structure characteristics of each hydrogel scaffold, the printed and cleaned scaffolds were pre-frozen overnight at -80℃, then freeze-dried in a vacuum freeze dryer until constant mass was achieved. They were then fixed to conductive adhesive and sputter-coated with gold. The morphology of the sample surface and pore wall regions was observed using field emission scanning electron microscopy at 5kV accelerating voltage. (Reference) Figure 2Microscopic images showed that each group of hydrogel scaffolds formed a uniformly distributed and interconnected porous structure with an intact overall morphology, and no obvious structural collapse or forming defects were observed.
[0049] Further quantitative analysis of pore size was performed on multiple random fields of view at the same magnification using ImageJ software. The results showed that the average pore size of the pure SilMA control group was 0.20±0.01 mm, while the average pore size of the 100 ng / mL, 300 ng / mL and 700 ng / mL loading groups after introducing different concentrations of L-leucine were 0.18±0.03 mm, 0.17±0.01 mm and 0.18±0.04 mm, respectively. No statistically significant differences were found among the groups.
[0050] It should be noted that the statistical object is the microporous structure on the surface of the pore wall after freeze-drying, rather than the 800μm printed macropores designed by CAD.
[0051] The above test methods and results fully demonstrate that, under the same photopolymerization 3D printing parameters, the loading of small molecule L-leucine did not cause damage to the microporous topology of the scaffold or a detectable shift. This highly consistent physical morphology effectively eliminates the interference that "pore size differences" may cause, thus providing an extremely reliable structural premise for subsequent simple comparison of osteogenic and vascularization biological effects caused by changes in material composition.
[0052] Experiment 1: The mass of each group of scaffolds after freeze-drying was precisely weighed using the alcohol displacement method and recorded as dry weight Wh. The scaffolds were then completely immersed in anhydrous ethanol and placed in a vacuum desiccator for 10 minutes to ensure that the ethanol fully penetrated into all pores. The scaffolds were then removed, and the surface ethanol was quickly blotted dry with filter paper and weighed immediately, recorded as wet weight Wa. The porosity level of each group of scaffolds was calculated according to the formula porosity = (Wa − Wh) / (alcohol density × gel volume).
[0053] like Figure 3 As shown in A and 3B, all four scaffolds exhibited a highly regular and interconnected porous structure. Quantitative measurements (Table 1) showed that the porosity of the pure SilMA control group was 52.1% ± 3%. After introducing L-Leu, the porosities of Examples 1, 2, and 3 were 54% ± 4%, 51% ± 3%, and 53% ± 4%, respectively. One-way ANOVA showed no statistically significant difference in porosity among the four groups. This result demonstrates that under identical 3D printing conditions, the loading of L-leucine (concentration range 0-700 ng / mL) did not disrupt or alter the overall three-dimensional interconnected porous structure of the SilMA hydrogel scaffold, with the porosity remaining stable within the ideal range of 50%-60%. This eliminates the interference factor of different structural parameters for all subsequent performance differences, ensuring the reliability of the performance comparison.
[0054] Experiment 2: A universal testing machine was used. Before testing, the free moisture on the surface of the support was gently absorbed with filter paper. The cylindrical support was placed vertically between the upper and lower pressure plates and uniaxially compressed at a constant rate of 1 mm / min until the strain reached 60%. The load-displacement data were recorded and converted into an engineering stress-strain curve. The compression modulus was calculated by taking the slope of the initial linear segment of the stress-strain curve.
[0055] Stress-strain curves as follows Figure 3 As shown in Figure C, the compressive modulus of the pure SilMA control group was only 0.20±0.03MPa, exhibiting the weak mechanical properties of traditional hydrogels. After the introduction of L-Leu, the compressive stiffness of the scaffold was significantly enhanced in a dose-dependent manner. The compressive moduli of the first, second, and third groups were 0.41±0.05MPa, 0.63±0.06MPa, and 0.85±0.07MPa, respectively (Table 1). Compared with the control group, the improvement of each experimental group was highly statistically significant.
[0056] These data clearly demonstrate that L-leucine, through physical encapsulation and enhanced intermolecular non-covalent interactions, can significantly improve the macroscopic mechanical properties of hydrogel networks without sacrificing the porous structure. Example 2 (300 ng / mL) achieved a modulus exceeding 0.6 MPa, providing necessary mechanical support for early repair of bone defects.
[0057] Experiment 3: Weigh the dry weight of the scaffold and record it as Wb. Immerse it completely in excess PBS and place it in a 37°C constant temperature shaker. Take out the sample at predetermined time points, such as 0.5, 1, 3, 6, 12, 24, and 48 hours. After blotting the surface liquid with filter paper, weigh the wet weight Ww immediately. The swelling rate is calculated according to the formula swelling rate = (Ww − Wb) / Wb.
[0058] Swelling kinetics curves as follows Figure 3 As shown in Figure D, all scaffolds rapidly absorbed water within 12 hours, subsequently reaching swelling equilibrium. The equilibrium swelling rate of the pure SilMA control group was approximately 550% after 24 hours. Loading with L-Leu significantly enhanced the water absorption capacity of the scaffolds. At 24 hours, the equilibrium swelling rates of groups 1, 2, and 3 (Examples 1, 2, and 3) reached approximately 610% ± 30%, 682% ± 28%, and 705% ± 32%, respectively, showing an increasing trend with increasing L-Leu concentration. This result demonstrates that the introduction of L-leucine greatly improves the hydrophilicity and hydration capacity of the hydrogel network. This enhancement stems from the strong affinity of the carboxyl and amino groups in the L-Leu molecule for water molecules, and their potential participation in forming a denser hydrogen bond network, enabling the scaffold to hold more bound water, thereby creating a highly hydrated, biomimetic microenvironment at the implantation site that promotes cell survival and material exchange.
[0059]
[0060] Experiment 4: Four sets of support structures were pre-frozen overnight at -80℃ and then freeze-dried until the mass stabilized. The initial dry weight of the samples after freeze-drying was recorded as D0. Each sample was then immersed in a centrifuge tube containing 1 mL of PBS and shaken at 37℃. Samples were removed on days 7, 14, 21, 28, 35, 42, 49, 56, and 63. After washing with PBS, the samples were freeze-dried to constant weight, and the remaining dry weight Dw was measured. The mass retention rate was calculated as follows: Retention rate (%) = Dw / D0 × 100%.
[0061] The test results showed that during long-term incubation under simulated physiological conditions, all groups of hydrogel scaffolds exhibited a slow, controllable, and time-dependent mass decay profile. In the early stages of degradation (days 7–14), the remaining mass ratio of all scaffolds remained consistently high at approximately 95%–98%, confirming the excellent structural stability of the photocrosslinked network in the early stages of implantation, providing reliable early mechanical support for bone defects. Subsequently, a relatively significant mass decrease occurred between days 28 and 35, with the degradation trend gradually leveling off between days 42 and 63. By the end of the observation period (day 63), the mass retention rate of the pure SilMA control group was approximately 89%, while the remaining mass of the L-leucine-loaded group was slightly lower, at approximately 87%–88%, with minimal difference between groups. Throughout the complete 8-week testing period, no significant structural instability or abnormal macroscopic fragmentation was observed in any of the scaffold groups.
[0062] The loading of L-Leu, by enhancing the hydrophilicity of the material, may have slightly promoted water penetration and hydrolysis, leading to a minor increase in the degradation rate, but without altering the overall "slow-controllable" degradation characteristics of SilMA. This degradation cycle matches the rate of bone tissue regeneration.
[0063] Experiment 5: Four groups of hydrogel scaffold samples with different formulations were pre-frozen overnight at -80℃ and then subjected to thorough dehydration in a freeze dryer until the sample quality stabilized and the samples were completely dry. The dried samples were then steadily fixed onto the dedicated stage of the contact angle measuring instrument, and the test area was carefully adjusted to ensure it was as flat as possible and precisely aligned with the instrument's optical imaging field of view. At room temperature, 5 μL of deionized water was vertically dropped onto the sample surface using a high-precision micro-syringe. After the droplet spread on the material surface stabilized, a high-resolution optical image was rapidly acquired, and the apparent water contact angle of the droplet was automatically calculated by the instrument's accompanying analysis software.
[0064] The results are as follows Figure 3As shown in E, F, and Table 2, the pure SilMA control group exhibited a water contact angle as high as 103.5°, indicating hydrophobicity. The introduction of L-Leu fundamentally altered the material's interfacial properties. The water contact angles of the first, second, and third examples decreased sharply to 67.6°, 57.2°, and 52.2°, respectively, showing a significant concentration-dependent decrease. This data corroborates the swelling experiment, confirming that L-leucine can significantly improve the hydrophilicity of the material surface. This superhydrophilic surface facilitates cell adhesion, spreading, and nutrient solution penetration, optimizing the initial interface for cell-material interactions.
[0065] Experiment Six: Each group of hydrogel scaffold samples was pre-frozen at -80℃ and then thoroughly freeze-dried. After freeze-drying, the sponge-like porous samples were ground into a uniform fine powder under dry conditions and spread evenly in the dedicated sample chamber of the Fourier transform infrared spectrometer. During testing, the characteristic infrared absorption spectra of the materials were collected in the wavenumber range of 4000–500 cm⁻¹. To ensure the acquisition of high-precision molecular vibrational signals, the instrument's test resolution was strictly set to 4 cm⁻¹, and the cumulative number of scans for each sample was set to ≥32, with signals superimposed to maximize the signal-to-noise ratio of the spectra. The obtained raw spectral data were uniformly imported into the instrument's accompanying analysis software for baseline correction and normalization to facilitate extremely rigorous inter-group comparative analysis.
[0066] Spectrum such as Figure 3 As shown in Figure H, all groups exhibited characteristic peaks of silk fibroin at ~1640 cm⁻¹ (amide I) and approximately 1500 cm⁻¹ (amide II). Characteristic absorption signals related to carbonyl (C=O) stretching vibrations were clearly observed in the 1700–1750 cm⁻¹ wavenumber range, which perfectly matches the carbonyl-containing structure intentionally introduced by the methacrylation process, chemically confirming its structural basis in participating in the formation of the photocrosslinked three-dimensional network framework. Key findings: The spectra of the L-Leu-loaded experimental groups did not show characteristic peaks attributed to newly formed chemical bonds between L-Leu and SilMA. However, the peak shape and absorption intensity of the composite material showed regular shifts and changes in the N–H / O–H stretching vibration region and the C–H related absorption region, suggesting enhanced hydrogen bonding interactions within the system. This indicates that L-Leu is mainly integrated into the SilMA network physically through non-covalent interactions such as hydrogen bonds, providing a molecular mechanism explanation for its simultaneously enhanced mechanical and hydrophilic macroscopic performance.
[0067]
[0068] Experiment 7: A rotational rheometer with parallel plate clamps was used for testing under a constant temperature of 25°C. After clamping the sample, a small amount of silicone oil was uniformly applied to the exposed edges of the hydrogel sample for liquid-phase edge sealing protection. The hydrogel sample was then securely placed between the parallel plates and precisely adjusted to the appropriate gap before starting the measurement program. First, an amplitude scan program was executed: the test angular frequency was fixed at 1 rad / s, and the strain scan range was set to 0.1%–100%, thereby accurately defining the linear viscoelastic region (LVR) of the material and recording the response trends of storage modulus and loss modulus with applied strain in real time. Subsequently, within the confirmed linear viscoelastic region, representative small strain parameters were selected, and a frequency scan program was executed: the angular frequency range was set to 0.1–100 rad / s, to further evaluate the time / frequency dependence behavior of the composite network.
[0069] Rheological spectra such as Figure 3 As shown in Figures 1 and 3J, and referring to Table 3, within the linear viscoelastic region, all samples exhibit a storage modulus greater than their loss modulus, behaving as elastic solids. Key differences: 1. The energy storage modulus of the L-Leu-loaded group was higher than that of the control group throughout the entire test range, and it increased with the increase of L-Leu concentration, indicating that the network resilience was enhanced.
[0070] 2. The intersection of the energy storage modulus and loss modulus of the load L-Leu group corresponds to a higher critical strain, indicating that the network can withstand greater deformation without being damaged.
[0071] 3. During frequency scanning, the energy storage modulus of the load L-Leu group exhibits a weaker frequency dependence, indicating that the network is more robust.
[0072] These data collectively demonstrate that the introduction of L-leucine significantly enhances the elasticity, mechanical stability, and deformation resistance of the SilMA hydrogel crosslinking network. This improved viscoelastic performance means that the scaffold can better maintain structural integrity in the complex dynamic mechanical environment in vivo, providing stable forces for tissue regeneration.
[0073]
[0074] While Example 1 showed the highest values for stiffness and fracture strain, Example 2 generally achieved the best balance between elasticity and stability. Its storage modulus was sufficiently high while maintaining excellent yield strength. This combination of high stiffness and good toughness is crucial for bone repair scaffolds that need to withstand complex, dynamic loads in vivo. This nonlinear optimization relationship (optimal overall rheological properties at 300 ng / mL) is an unexpected technical effect of L-Leu functionalization.
[0075] Example 1: To verify the biosafety of the SilMA@L-Leu composite hydrogel scaffold described in this invention for key target cells of bone repair and its supporting effect on cell growth and proliferation, this efficacy example used bone marrow mesenchymal stem cells (BMSCs) and human umbilical vein endothelial cells (HUVECs) as a two-cell in vitro model. The four groups of scaffolds obtained in the control example, example 1, example 2, and example 3 were evaluated using CCK-8 cell proliferation assay and Calcein-AM / PI live-dead cell double staining method.
[0076] 1. The effect of scaffolds on cell proliferation was evaluated using the material extraction method. Extracts from each group of hydrogel scaffolds were co-cultured with BMSCs and HUVECs seeded in 96-well plates. CCK-8 reagent was added on days 1, 3, and 5 of culture, and absorbance at 450 nm was measured.
[0077] like Figure 4 As shown in Figures A and 4B, on days 1, 3, and 5 of culture, the cell viability curves of both the experimental and control groups showed a healthy growth trend with a gradual increase over time, and no obvious cytotoxic signals were observed overall. Crucially, compared to the control group, the L-Leu functionalized groups (Examples 1, 2, and 3) showed significantly higher CCK-8 readings at all detection time points. Particularly on days 3 and 5, the increase in cell viability in Examples 2 and 3 was more pronounced, with statistically significant differences. This result definitively suggests that the specific introduction of L-leucine is not only safe and non-toxic but also serves as an effective bioactive signal, significantly enhancing the metabolic activity of target cells and promoting cell proliferation.
[0078] 2. To further and more intuitively assess cell viability and spatial distribution, this invention employs a Transwell indirect co-culture system for dual fluorescence staining of live and dead cells. On days 1, 3, and 5 of co-culture, the Calcein-AM / PI staining results clearly and further confirm the extremely excellent cell compatibility of this material system. Figure 4 As shown in C-4F, green fluorescent Calcein-positive live cells dominated the field of view in all groups, while red fluorescent PI-positive dead cells were rare. Although morphological observation showed that the L-Leu-loaded groups (Examples 1, 2, and 3) had significantly higher cell spreading density and a wider distribution area of live cells, quantitative survival statistics indicated that the overall cell survival rate of each group remained consistently at a very high level, with no statistically significant differences between groups. This data rigorously confirms that the physical addition of L-leucine did not introduce any additional cytotoxicity into the matrix network.
[0079] The aforementioned in vitro tests based on a two-cell model fully demonstrate that the SilMA@L-Leu composite hydrogel scaffold constructed in this invention, while maintaining the excellent biocompatibility of natural silk fibroin as a substrate, can significantly promote the proliferation and growth of bone marrow mesenchymal stem cells and vascular endothelial cells through the release of L-leucine. This not only establishes the extremely high biocompatibility of this scaffold as an in vivo implant, but also lays a reliable cellular dynamic basis for the subsequent dual-coupled repair effect of osteogenic-angiogenic processes in the complex in vivo microenvironment.
[0080] Example 2: To systematically verify the osteogenic induction effect of L-leucine-functionalized SilMA hydrogel scaffolds on BMSCs, this efficacy example evaluated the four scaffolds in vitro from three dimensions: early differentiation initiation, late mineralization deposition, and expression of key osteogenic functional proteins.
[0081] 1. Based on the confirmation that the material has good cell compatibility, alkaline phosphatase (ALP) activity and staining (day 14 of culture) and Alizarin Red S (ARS) mineralization staining (day 21 of culture) were used for evaluation.
[0082] like Figure 5 As shown in A, 5B, 5E, and 5F, ALP staining results showed that the L-Leu functionalized scaffold significantly enhanced ALP staining signal compared to the control group. Specifically, on day 14 of induction culture, the Example 2 (300 ng / mL) group exhibited the most uniform and strongest dark staining intensity. Corresponding quantitative results showed that ALP activity increased with increasing dose in the low to medium loading range, reaching a high level at 300 ng / mL; when the concentration increased to 700 ng / mL, this increase no longer increased further. ARS staining showed that by day 21, the Example 2 (300 ng / mL) group formed the densest calcium nodule deposits at the material-cell interface, and its quantitative analysis also indicated that the matrix calcification level of this group was superior to that of the control group and the low-dose group.
[0083] 2. Immunofluorescence was used to observe cells in the culture system in situ to detect the expression of Runx2, a key transcription factor for early osteogenic formation, and its downstream key bone matrix proteins (type I collagen COL-1 and osteocalcin OCN).
[0084] like Figure 5As shown in C, 5D, and 5G-N. Compared to the control group, the fluorescence signals of Runx2, COL-1, and OCN in the L-Leu-loaded groups (Examples 1, 2, and 3) were significantly enhanced. Particularly in the preferred dose group of Example 2 (300 ng / mL), the fluorescence signal of overall osteogenic-related proteins was most prominent and uniform. This molecular-level evidence suggests that moderate doses of L-Leu are more conducive to maintaining sustained osteogenic differentiation and accelerate the formation and effective accumulation of bone matrix-related proteins at the transcriptional and translational levels.
[0085] The above multi-dimensional verification results based on different stages and levels conclusively demonstrate that the SilMA@L-Leu hydrogel 3D scaffold constructed in this invention not only provides passive physical support in vitro, but also possesses active biological induction function. It can efficiently activate and maintain the osteogenic differentiation and mineralization maturation trajectory of BMSCs, and clearly defines 300 ng / mL as the preferred loading concentration for achieving the best overall osteogenic performance.
[0086] Example 3: 1. Immunofluorescence technique was used to detect the expression of key angiogenesis markers VEGF and CD31 in situ.
[0087] like Figure 6 As shown in A, 6B, 6D, and 6G-6K. Immunofluorescence results showed that the fluorescence signals of VEGF and CD31 in the L-Leu-loaded group were significantly enhanced overall; further quantitative analysis of fluorescence intensity showed that the expression levels of the above markers showed a clear upward trend among different doses, with the highest fluorescence expression level in the Example 3 (700 ng / mL) group.
[0088] 2. The Matrigel tube formation experiment was used to confirm the material's ability to induce endothelial cells to assemble into a network on a macroscopic scale, and to quantitatively analyze the number of tube nodes and the total tube length.
[0089] like Figure 6 As shown in C-6F, the experimental results show that, compared with the control group, the L-Leu functionalized scaffold significantly promoted the three-dimensional network assembly of HUVECs. However, crucially and unexpectedly, different loading doses exhibited a non-linear dose-response relationship in terms of actual network formation quality: at the 6h and 8h observation time points, the Example 2 group (300 ng / mL) induced the formation of the most connected and structurally complete capillary-like network, which comprehensively and significantly outperformed other groups in core topological indicators such as the number of tube-forming nodes and the total tube length. In contrast, although the Example 3 group (700 ng / mL) showed a stronger molecular response in the aforementioned immunofluorescence assay, it failed to bring further gains in actual tube-forming topological indicators.
[0090] This embodiment demonstrates that the small molecule L-leucine exists in a very delicate nonlinear kinetic equilibrium when regulating endothelial cell vascularization. In the system of this invention, a loading concentration of 300 ng / mL achieves the most perfect balance between "activation of underlying molecular signals" and "construction of macroscopic functional network topology".
[0091] Based on the optimal osteogenic and mineralization effect of 300 ng / mL on BMSCs in Example 2, 300 ng / mL was established as the optimal / critical preferred loading concentration for achieving "efficient coupling of osteogenic and angiogenic processes".
[0092] Example 4: This effective embodiment uses a Transwell chamber to establish an indirect co-culture chemotactic model and a scratch assay to evaluate the chemotactic attraction of L-leucine released from the material to cells.
[0093] 1. For example Figure 7 As shown in A and 7C. Experimental results showed that, compared with the control group, the L-Leu loading group exhibited a significant increase in the number of transmembrane-migrating BMSCs at 24 hours. Quantitative counting results indicated that the total number of migrating cells in Examples 1, 2, and 3 was significantly higher than that in the control group. Particularly noteworthy was the Example 2 (300 ng / mL) group, which showed the strongest promoting effect at both time points; however, when the concentration increased to 700 ng / mL, no further increase in the number of migrating cells was observed.
[0094] like Figure 7 As shown in E and 7G. In the test targeting endothelial cells, the functionalized chemotactic response of L-Leu was more rapid. At 12 h, the loaded group significantly increased the number of HUVECs migrating across the membrane. Highly consistent with the results for BMSCs, the number of migrating endothelial cells in the Example 2 (300 ng / mL) group remained at the highest level, while the high-dose group of 700 ng / mL also did not show any additional chemotactic gain.
[0095] 2. Validation of planar migration capability based on scratch testing, such as... Figure 7 As shown in B, 7D, 7F, and 7H. In both BMSCs and HUVECs cell models, morphological observation and quantitative migration statistics 24 hours after scratching yielded consistent conclusions: compared to the slow edge crawling in the control group, the scratch wounds in each L-Leu-loaded group closed more rapidly and completely. Among all tested groups, the second example (300 ng / mL) group exhibited the largest wound closure amplitude and the highest cell migration rate.
[0096] The migration experiments based on the dual-cell model and dual-evaluation system demonstrated that the SilMA@L-Leu composite hydrogel scaffold constructed in this invention can not only "nourish cells (cell compatibility)" and "induce cells (differentiation and tube formation)", but also "attract cells (chemotactic recruitment)" with extremely high efficiency in the earliest stage of repair.
[0097] More importantly, migration experiments further revealed a clear nonlinear dose-response relationship and optimal dose range in the regulation of cell behavior by L-leucine. Within the test range of 100–700 ng / mL, a concentration of 300 ng / mL showed excellent comprehensive promoting effects on the bidirectional chemotactic recruitment of both BMSCs and HUVECs.
[0098] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely preferred examples and are not intended to limit the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.
Claims
1. A bone repair 3D printing material, characterized in that: The 3D printing material is composed of photocurable modified silk fibroin and bioactive small molecules, wherein the photocurable modified silk fibroin is methacrylamide silk fibroin. The bioactive small molecules are branched-chain amino acids. The bioactive small molecules are uniformly dispersed in the precursor solution of the photocurable modified silk fibroin by physical blending and then anchored to the gel network by non-covalent interactions after photocrosslinking. The nominal loading concentration of the bioactive small molecule in the precursor solution ranges from 100 ng / mL to 700 ng / mL; The branched amino acid is selected from L-leucine.
2. The bone repair 3D printing material according to claim 1, characterized in that: The nominal load concentration is 300 ng / mL.
3. A bone repair scaffold, characterized in that, The scaffold is obtained by photopolymerization 3D printing using a bone repair 3D printing material according to any one of claims 1-2. The scaffold has a porous structure constructed by computer-aided design, with a macroscopic pore size of 500-1000μm and a porosity of 40%-60%.
4. A method for preparing a bone repair scaffold as described in claim 3, characterized in that, Includes the following steps: Step 1: Dissolve the photoinitiator and bioactive small molecules in a buffer solution, add the photocurable modified silk fibroin powder, mix and dissolve under light-protected conditions to obtain a homogeneous and clear composite precursor solution; Step 2: Load the composite precursor solution into the material tank of the photopolymer 3D printer. Based on digital light processing technology, solidify layer by layer under preset light intensity and exposure time to form a wet hydrogel scaffold with preset macroscopic channels. Step 3: Immerse the wet hydrogel scaffold in an alcohol solution to induce a conformational change in silk fibroin and sterilize it. Then rinse and replace it with buffer solution to obtain the bone repair scaffold.
5. The preparation method according to claim 4, characterized in that: In step one, the mass-volume concentration of the photocured modified silk fibroin in the precursor solution is 15%-25%.
6. The preparation method according to claim 4, characterized in that: In step two, the preset light intensity is 5-10 mW / cm², and the single-layer exposure time is 5-20 s.
7. The preparation method according to claim 4, characterized in that: In step three, the alcohol solution used for the alcohol treatment has a concentration of 50%-100% and a treatment time of 10-60 minutes.
8. The preparation method according to claim 4, characterized in that: In step two, the photopolymer 3D printer is a DLP printer, an SLA printer, or an LCD printer.
9. The use of a bone repair 3D printing material as described in any one of claims 1-2 in the preparation of bone tissue engineering scaffolds, drug sustained-release carriers, or cartilage repair materials.